1975
DOI: 10.1099/0022-1317-27-1-1
|View full text |Cite
|
Sign up to set email alerts
|

A Single Radial Haemolysis Technique for the Measurement of Influenza Antibody

Abstract: SUMMARYA single radial haemolysis in gel technique has been developed for the detection and measurement of antibody to influenza haemagglutinin. The method combines the sensitivity of haemagg]utination-inhibition with the accuracy of single radial diffusion. It is simple, quick, reproducible, does not require purified or concentrated virus, and is unaffected by non-specific inhibitors. The method is particularly suitable for the routine screening of large numbers of serum samples, and may have application also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
2
5

Year Published

1977
1977
1988
1988

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 4 publications
6
61
2
5
Order By: Relevance
“…In recent years, SRH has been extensively employed for the measurement of antibody against both A and B viruses (Vaananen et al 1976;Delem & Jovanovic, 1978;Chakraverty, 1980;Goodeve et al 1983) and the test correlates well with the HI for the measurement of serum antibodies to influenza A viruses (Russell et al 1975;Schild et al 1975;Farrohi et al 1977;Jennings et al 1984). In the present studies the two tests showed good correlation for the measurement of both HI and H3 antibodies.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In recent years, SRH has been extensively employed for the measurement of antibody against both A and B viruses (Vaananen et al 1976;Delem & Jovanovic, 1978;Chakraverty, 1980;Goodeve et al 1983) and the test correlates well with the HI for the measurement of serum antibodies to influenza A viruses (Russell et al 1975;Schild et al 1975;Farrohi et al 1977;Jennings et al 1984). In the present studies the two tests showed good correlation for the measurement of both HI and H3 antibodies.…”
Section: Discussionsupporting
confidence: 67%
“…The single radial haemolysis (SRH) test (Russell, McCahon and Beare, 1975;Schild, Pereira & Chakraverty, 1975) is now widely used for the determination of antibody to influenza A and B viruses in both vaccine studies and following natural infections (Vaananen et al, 1976;Farrohi et al 1977;Delem & Jovanovic, 1978;Cretescu et al 1979;Chakraverty, 1980;Grilli & Davies, 1981;Oxford, Yetts & Schild, 1982;Yamagishi et al 1982; Goodeve, Jennings and Potter, 1983). It is a test both simple and reproducible, rapid to perform, and more sensitive than the conventional haemagglutination-inhibition (HI) test (Russel, McCahon & Beare, 1975;Oxford et al 1982;Goodeve, Jennings & Potter, 1983;Jennings et al 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is rapidly accumulating to support the value of the SRH test in assays of anti-viral antibodies. In influenza virus, it is antibody to haemagglutinin which produces efficient SRH reactions (Schild et al 1975b;Russell et al 1975). It has also been shown that antibody to neuraminidase can be detected (Callow & Beare, 1976) but anti-neuraminidase antibody gives haemolysis only if high concentrations of antigen are added to erythrocytes (Schild et al 1975b).…”
Section: Comparison Of Results Of Srh and Hi Testsmentioning
confidence: 99%
“…The development of the single-radial-haemolysis (SRH) technique for the detection of antibody to influenza haemagglutinin (Schild, Oxford & Virelizier 1975a;Schild, Pereira & Chakraverty 1975b; Russell, McCahon & Beare, 1975), has led to the application of this method to other haemagglutinating viruses. It has been successfully used for rubella virus (Skaug, 0rstavik & Ulstrup, 1975; Strannegard, Grillner & Lindberg, 1975) and for mumps virus (Grillner & Blomberg, 1976; Viininen, Hovi, Helle & Penttinen, 1976).…”
Section: Introductionmentioning
confidence: 99%